Media based on ROTELA-an innovation for teaching Pancasila and Civic Education - Murdiono, Mukhamad; Kuncorowati, Puji Wulandari; Arpannudin, Iqbal; Suyato, Suyato (Jurnal Civics: Media Kajian Kewarganegaraan, 2023)
Pancasila and Civic Education Subjects (PPKn) in junior high schools are prerequisite subjects with abstract material. To facilitate understanding of the values of Pancasila, it is necessary to develop learning media to make it easier for students to understand and apply the values of Pancasila as the way of life of the Indonesian people. This research aims to develop learning media that can be used by teachers in teaching Pancasila and Civic Education in junior high schools. This study uses a research and development method to develop learning media ROTELA (wheel guess the image of Pancasila). This research was implemented in State Junior High School in Yogyakarta City. The research subjects were Pancasila and Civic Education teachers and VIII grade students. Data collection techniques used in this study were observation, interviews, and documentation. Data analysis used qualitative and quantitative analysis. The development research follow the steps of Borg and Gall. The results showed that the media based on ROTELA were developed very feasible to be used in teaching Pancasila dan Civic Education in junior high school for Pancasila as the way of life of the Indonesian people. The results of the validation of the material experts showed 90%, and media experts 96.6%.